Kapasitas dan Stabilitas Senyawa Antibakteri Ekstrak Kulit Kayu Akway (Drimys piperita) terhadap Pertumbuhan Escherichia coli Patogenik - Roreng, Mathelda Kurniaty; Cepeda, Gino Nemesio (Fakultas Teknologi Pertanian Universitas Jember, 2025)
Drimys piperita known with local name of akway by Sougb tribe communities lived in district of Anggi, regency of Pegunungan Arfak, Province of West Papua. The. Plant was used as tradisional medicines for treating malaria and enhancing vitality. The objectives of research were to know the group of compounds composed of akway bark ethanolic extracts, potency of akway extracts as an antibacterial agent on inhibiting growth of pathogenic Escherichia coli and stability of antibacterial compounds of extract on heating of 100ºC for 0−20 minutes. Qualitative assays of compounds composed extract were done on compound class of terpenoids, alkaloids, saponins, flavonoids, tannins dan steroids. Antibacterial capacity and stability assays were done by using agar well diffusion method. The results indicated that ethanolic extracts of akway content compound class of terpenoids, alkaloids, saponins, flavonoids, and tannins. Ethanolic extracts of akway could inhibit growth of pathogenic Escherichi coli ATCC 43894 and ATCC10798 on minimum inhibiting concentration of 1.05% and 1.26% respectively. The antibacterial properties of akway extract was stable on heating of 100ºC for 0−20 minutes. Ethanolic extracts of akway bark was potential as source of natural antibacterial agent for inhibiting growth of pathogenic E. coli.Keywords: antibacterial capacity, Drimys piperita, extracts, stability